Analisis Kelayakan Usaha Penggemukan Sapi Potong di Kelompok Tani Selo Mukti Desa Banyumeneng Kecamatan Mranggen Kabupaten Demak - Prasetyo, Septian Dwi; Fachriyan, Hilmi Arija; Hastuti, Dewi; Subekti, Endah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to determine the total cost, revenue, income, and R/C ratio. The research was conducted from January to June 2024. The sampling method used was purposive sampling, with 20 selected farmers as research samples. The analysis method employed was business analysis. The data used consisted of primary and secondary data, collected through observation and interviews. The results showed that the cattle fattening business involved 54 cattle, with a fattening period of one cycle lasting six months. The total cost for 20 respondents amounted to Rp. 1,085,540,776 per cycle, consisting of total variable costs of Rp. 1,072,194,880 and total fixed costs of Rp. 13,345,896. The total revenue was Rp. 1,647,450,000, while the income reached Rp. 561,909,224. The monthly income per respondent was Rp. 4,682,577, with an average of three cattle raised. The R/C ratio was 1.52, meaning that for every Rp. 1 spent, the farmers earned Rp. 1.52. It can be concluded that the cattle fattening business in the Selo Mukti Farmers Group, Banyumeneng Village, Mranggen District, Demak Regency, is feasible to run.